Approaching the macro-micro Interface in transitional societies: Evidence from Bulgaria - Snejina Michailova (Journal for East European Management Studies, 1996)
The article approaches the dynamics of the macro-micro between organizational environment and organization) in a dramatically changing command society. It is based on the empirical findings of a case study conducted by the author in Bulgaria in 1994. Kanter et al.'s organizational change model (1992) has been selected as theoretical framework for studying. The model is confronted with the collected field data and on this basis modifications in the model are suggested. – – Der Beitrag setzt sich mit der Dynamik des Makro-Mikro Interfaces (zwischen Organisationsumfeld und Organisation) in einer sich dramatisch verändernden Kommandogesellschaft auseinander. Er basiert auf den empirischen Ergebnissen einer Fallstudie, die die Autorin 1994 in Bulgarien durchgeführt hat, wobei das Modell des Organisationswandels von Kanter et al. (1992) den theoretischen Rahmen für die Untersuchung bildet. Das Modell wird konfrontiert mit den gesammelten Daten der Fallstudie, und auf dieser Grundlage werden Modellmodifikationen vorgeschlagen.
Keywords: 650